Rural dairy technology. Experiences in Ethiopia - O'Mahony, F. (International Livestock Centre for Africa, 1988)
This manual is intended as a teaching aid for extension level technicians. Deals with rural milk processing at individual smallholder or small producers cooperatives levels using experiences from Ethiopia. Concentrates on traditional products, i.e, product that are easily made, need little specialised equipment and easily adapted to the rural processing plant.